DETERMINANT EXPORT VOLUME OF CRUDE PALM OIL (CPO) IN INDONESIA AND MALAYSIA IN THE EUROPEAN UNION MARKET - Mirawati Yanita; Suandi Suandi (Socio-Economics/Agribusiness Department, 2023)
Crude Palm Oil (CPO) is one of the leading export commodities of Indonesia and Malaysia. After India, the European Union has become the top Indonesian and Malaysian CPO export market share. However, Indonesian and Malaysian CPO exports indicate constraints on CPO exports to the European Union (E.U.). In addition, the European Union also issued a Renewable Energy Directive policy that can impact CPO exports. Therefore, this study is at 1) Describes the development of Indonesian and Malaysian CPO export volumes in the European Union from 1990 to 2019. 2) Analyze The determinants of Indonesian and Malaysian CPO export volumes in the EU Market from 1990 to 2019 3) Describe the impact of the Renewable Energy Directive (RED) policy on Indonesian and Malaysian CPO exports in the European Union Market. This study's data type is secondary data in an annual time series with a time range from 1990 to 2019. The study was analyzed descriptively, and the Regression Analysis was multiple. The results showed that the development of Indonesian and Malaysian CPO export volumes in the European Union fluctuated but tended to increase from 1990 to 2019. Indonesia's CPO export volume in the European Union significantly affects International CPO prices, real exchange rates, and RED Policies. In contrast, the volume of Malaysian CPO exports in the European Union significantly influences International CPO prices and real exchange rates. The RED policy positively influenced the volume of Indonesian and Malaysian CPO exports in the European Union before and after enacting the policy. In the future, it is necessary to increase the use of CPO in the country and develop palm oil derivative products to get priority and sustainability.